Simulating streamflow in the Upper Halda Basin of southeastern Bangladesh using SWAT model. Issue 1 (2nd January 2020) - Raihan, Farzana; Beaumont, Linda J.; Maina, Joseph; Saiful Islam, Akm; Harrison, Sandy P.
ABSTRACT: Most catchments in tropical regions are ungauged and data deficient, complicating the simulation of water quantity and quality. Yet, developing and testing hydrological models in data-poor regions is vital to support water management. Here, we used the Soil and Water Assessment Tool (SWAT) to predict stream runoff in Halda Basin in Bangladesh. While the calibrated model's performance was satisfactory (R 2  = 0.80, NSE = 0.71), the model was unable to track the extreme low flow peaks due to the temporal and spatial variability of rainfall which may not be fully captured by using data from one rainfall gauging station. Groundwater delay time, baseflow alpha factor and curve number were the most sensitive parameters influencing model performance. This study improves understanding of the key processes of a catchment in a data-poor, monsoon driven, small river basin and could serve as a baseline for scenario modelling for future water management and policy framework.